Rights and Legal Position of Children out of Wedding in Civil Law - Sukadana, Dewa Ayu Putri (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Legal status of illegitimate children according to the Civil Code (KUH Perdata), especially regarding their civil status and inheritance rights. In the Indonesian civil law system, illegitimate children only have a legal relationship with their biological parents if they have been legally recognized as regulated in Article 280 of the Civil Code. Illegitimate children are divided into three categories: adulterous children, incestuous children, and illegitimate children who can be recognized. Recognition of illegitimate children is constitutive, namely creating a new legal status that grants inheritance rights and other civil rights to the parents who recognize them. However, adulterous children and incestuous children cannot be recognized and do not have inheritance rights, except for the right to adequate living expenses. Although recognized illegitimate children have inheritance rights, their position is still different from legitimate children, both in terms of inheritance portion and family relationship. This discussion emphasizes the importance of recognition as a condition for the formation of a legal relationship between illegitimate children and parents, as well as its impact on inheritance rights based on the provisions of the Civil Code